The Design Thinking to Improving on Scientific Argumentation Skills: A Systematic Literature Review - Rina Agustini Sitohang; I Wayan Redhana; Putu Artawan (Jurnal Penelitian Pendidikan IPA, 2025)
Students scientific argumentation skills remain relatively low, posing both global and national educational challenges that require innovative solutions. Effective learning methods to foster these skills are still limited and not yet optimal. This study aimed to identify research trends in the application of design thinking in learning, the learning outcomes achieved, the subjects most frequently using design thinking, and its contribution to developing scientific argumentation skills. The method used in this study is the Systematic Literature Review (SLR) with PRISMA analysis of 20 relevant articles. The articles were obtained from two databases, namely Google Scholar and PubMed with a publication range between 2020 - 2025. The article selection process was carried out to collect, analyze and compile findings on the application of the design thinking method in learning. The findings of the Systematic Literature Review show that the most dominant research trend uses quantitative methods. Design thinking has a positive impact on creativity, critical thinking skills, learning outcomes, numeracy, learning interest, motivation, and scientific attitudes. Design thinking tends to be applied more in the context of science learning, especially in science and biology subjects. In addition, design thinking not only increases student engagement and creativity, but also significantly trains and strengthens scientific argumentation skills which are essential in science learning.